PENGARUH PUPUK KOMPOS TUMBUHAN KIPAHIT (Tithonia diversifolia) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica rapa L.) - Arlita, Prili Hardini Nur; Purnomo, Sulistyo Sidik; Subardja, Vera Oktavia (Percetakan Umi Toaha Makassar, 2025)
Pakcoy is in great demand by the public because it has important health benefits. In the context of using organic fertilizer, kipahit plant fertilizer can be used as a growth medium for pak choy plants. This research aims to obtain a treatment dose of kipahit plant compost that can provide the best results for the growth of pak choy plants (Brassica rapa L.). This experiment was carried out on the Telaga Desa land located in the KIIC Industrial Area, Karawang Regency, during the period June to July 2024. The research method applied was an experimental method with a Single Factor Randomized Block Design (RAK). There were 6 treatments, which were repeated 4 times, using kipahit plant compost as media. The results of the study showed that there was no significant effect of giving a dose of kipahit plant compost on all observed parameters. In particular, the P3 treatment (compost fertilizer dose of 15 tons/ha) gave the best results in plant height, number of leaves, root length, and plant fresh weight.